Human capital systems, analytics, and data mining - Hughes, Robert Clayton (Boca Raton : CRC Press, Taylor & Francis Group, 2019)
"This book fills a void in the systems and big data space with regard to human capital systems, data architecture, analytics, and systems. It is designed both as a text for graduate level courses in human resource systems, human capital analytics, and data mining as well as a resource for human capital analytical professionals in the course of ongoing contemporary research in all functional areas of human capital, including compensation, benefits, talent acquisition, and performance"--
Human capital management systems -- Human capital management system components -- Database systems, concepts and design -- Dimensional modeling -- Reporting and analytics with multidimensional and relational databases -- Online analytical processing and the OLAP cube multidimensional database -- Multidimensional OLAP database project with SQL server analytical services -- Multidimensional cube analysis with Microsoft Excel and SQL server analysis services -- Data mining -- Project management.
Includes bibliographical references and index.
CSE
Parama
Keywords: Human capital -- Management -- Data processing; Personnel management -- Data processing; Personnel management -- Statistical methods; Database management; Data mining; Computer science